Holocene winds of the vestfold hills, Antarctica - Pickard, John (New Zealand Journal of Geology and Geophysics, 1982)
Transverse erosional marks are common on dolerite dikes and gneiss country rock in the Vestfold Hills (68°30′S, 78°00′E). Ventifact faces are also common on boulders and rock outcrops. Orientations of the marks and of ephemeral snow drifts behind small rocks coincide and are equal to the present mean wind direction of 67°T. Orientations of ventifacts also coincide with the present wind direction. The erosional marks have a maximum possible age of 8000 years over most of the hills but a maximum of 2000 years at 1 site. An inactive sand dune, with fossil shells radiocarbondated at c. 4000 years old, shows the same orientation. Wind direction during the Holocene, since ice-cap retreat 8000 years ago; has remained essentially constant at 67°T.